Race, religion, and law in colonial India : trials of an interracial family - Mallampalli, Chandra, 1965- (Cambridge ; New York : Cambridge University Press, 2011)
'Through a landmark court case in mid-nineteenth century colonial India, this book investigates hierarchy and racial difference in the British encounter with Indian society'--
'How did British rule in India transform persons from lower social classes? Could Indians from such classes rise in the world by marrying Europeans and embracing their religion and customs? This book explores such questions by examining the intriguing story of an interracial family who lived in southern India in the mid-nineteenth century. The family, which consisted of two untouchable brothers, both of whom married Eurasian women, became wealthy as distillers in the local community. When one brother died, a dispute arose between his wife and brother over family assets, which resulted in a landmark court case, Abraham v. Abraham. It is this case which is at the center of this book, and which Chandra Mallampalli uses to examine the lives of those involved and, by extension, of those - 271 witnesses in all - who testified. In its multilayered approach, the book sheds light not only on interracial marriage, class, religious allegiance, and gender, but also on the British encounter with Indian society. It shows that far from being products of a'civilizing mission' who embraced the ways of Englishmen, the Abrahams were ultimately - when faced with the strictures of the colonial legal system - obliged to contend with hierarchy and racial difference'--
Remembering family -- Embodying'Dora-hood' : the brothers and their business -- A crisis of trust : sedition and the sale of arms in Kurnool -- Letters from Cambridge -- The path to litigation -- Litigating gender and race : Charlotte sues at Bellary -- Francis appeals : the case for cultural continuity -- Choice, identity, and law : the decision of London's Privy Council.
Includes bibliographical references (p. 249-261) and index.
Keywords: Abraham, Matthew, -- d.1842 -- Trials, litigation, etc; Inheritance and succession -- India -- Bellary (District) -- History -- 19th century; Legal polycentricity -- India -- Bellary (District) -- History -- 19th century; Bellary (India : District) -- Social conditions -- 19th century; Abraham v. Abraham, 9 Moore's Ind. App. 199 (1863) (Judicial Committee of the Privy Council)